1990
DOI: 10.1073/pnas.87.9.3542
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of cDNA for the carcinoma-associated antigen GA733-2.

Abstract: Defined by monoclonal antibody GA733, the GA733-2 antigen is a cell surface 40-kDa glycoprotein associated with human carcinomas of various origins. Molecular clones for the GA733-2 antigen were isolated from a colorectal carcinoma cell line cDNA library using the high-efficiency COS cell expression system. A 1.4-kilobase cDNA species was enriched by immunoselection with monoclonal antibody. The authenticity of individual clones was established by immunologic and sequence criteria. At the amino acid sequence l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
109
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(113 citation statements)
references
References 26 publications
3
109
1
Order By: Relevance
“…Within the extracellular part there is an EGF-like domain (AA 26 ± 48) and a thyroglobin-like repeat (AA 60 ± 122). Corresponding to the human and the mouse molecule (Bergsagel et al, 1992;Bjork et al, 1993;Szala et al, 1990b). D5.7A has 12 conserved cystein residues two consensus sequences for phosphorylation and two potential N-glycosylation sites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the extracellular part there is an EGF-like domain (AA 26 ± 48) and a thyroglobin-like repeat (AA 60 ± 122). Corresponding to the human and the mouse molecule (Bergsagel et al, 1992;Bjork et al, 1993;Szala et al, 1990b). D5.7A has 12 conserved cystein residues two consensus sequences for phosphorylation and two potential N-glycosylation sites.…”
Section: Resultsmentioning
confidence: 99%
“…Like EGP314 (Bergsagel et al, 1992;Bjork et al, 1993;Linnenbach et al, 1993;Perez and Walker, 1989;Strnad et al, 1989;Szala et al, 1990b) it is a type 1 transmembrane molecule with 12 conserved cystein residues and two N-glycosylation sites. Furthermore, an EGF-like domain and a thyroglobin-like repeat are conserved (Fornaro et al, 1995;Kiefer et al, 1991;Malthiery and Lissitzky, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clones were tested for tumorigenicity in Balb / c mice. A tumorigenic clone was transfected with the human GA733 -2 cDNA 22 and selected with G418 (Gibco BRL, Grand Island, NY ). FACS analysis revealed H -2k d expression in $98% of the transfectants and GA733 Ag expression in $86% of the cells in vitro (not shown ).…”
Section: Tumor Cellsmentioning
confidence: 99%
“…MAbs directed against EGP-2, such as C017-lA, KS1/4 and MOC3 1, have been studied extensively in diagnostic and therapeutic approaches in cancer (Lobuglio et al, 1986;Elias et al, 1990; Kroesen et al, 1993;Herlyn et al, 1994;Kosterink et al, 1995). The human EGP2 cDNA was independently cloned by different research groups (Bumol et al, 1988;Strnad et al, 1989;Szala et al, 1990) and, more recently, its gene structure on chromosome 4q has been partly determined. Comparison of GA733-2 gene sequences with the previously established cDNA sequence revealed that this gene consists of nine exons interspersed by introns of variable length (Linnenbach et al, 1993).…”
mentioning
confidence: 99%